Heat transfer enhancement of bioglycol/water based TiO2 and SiO2 nanofluids in a flat tube with twin twisted tapes - Abdolbaqi, Mohammed Khdher (2017)
The research on heat transfer has been receiving important attention since long time ago and has found applications in several areas such as the cooling of electronic devices, manufacturing systems and solar energy systems. The effective passive methods for heat transfer augmentation are the additive technique for nanofluid and swirl flow devices, are acquiring great attention in order to enhance the thermal performance of the heat exchangers. Among the swirl flow devices which are used to create swirl or secondary flow, twisted-tape inserts are very popular because of their good thermal performance. The increasing demand for more efficient heat transfer fluids in many applications has been led to enhance heat transfer to meet the cooling challenge necessary. Nanofluid is a relatively new engineering material consisting of the nanometre-sized additives and base fluids, has gained extensive attention due to its role in improving the efficiency of thermal systems. Although, there are many studies of nanofluids with different types of base fluid such as water, Ethylene glycol (EG) and Propylene glycol (PG), there are very limited studies of using nanofluids with BioGlycol as a base fluid. While, BioGlycol (BG) showed more advantages compared to water Ethylene glycol (EG) and Propylene glycol (PG), for instance, a much lower freezing point and higher boiling point than water, provided lower viscosity compared to Propylene glycol (PG) and Ethylene glycol (EG), has greater thermal stability while possessing similar or better thermophysical properties compared to Propylene and Ethylene glycols and non-toxic renewable sourced fluid. The aim of the present study is to evaluate the heat transfer coefficient and pressure drop of BioGlycol/Water based TiO2 and SiO2 nanofluids for flow in a flat tube and with twin twisted tapes experimentally and numerically. For this evaluation, the thermophysical properties of TiO2 and SiO2 nanofluids are prepared at different volume concentrations and temperatures. A test rig was fabricated with the facility to heat the liquid by wrapping with two nichrome heaters on the flat tube with an option to insert the twisted tapes. Experiments are carried out to determine the Nusselt number and friction factor with BioGlycol/water of (20/80)% mixture ratio by volume based TiO2 and SiO2 nanofluids at (30, 50 and 70oC) in the turbulent range of Reynolds number (Re) for flow in a flat tube and with twin twisted tapes. The maximum enhancement in the heat transfer was 28.2% for 1.0% TiO2 nanofluids at Re = 21,194 and temperature 50oC. However, the maximum heat transfer enhancement was 29.3% of SiO2 nanofluids with 2.0% volume concentrations at Re = 21,169. It can be stated that the heat transfer enhancement depends on the nanoparticles concentration and operating temperature of the nanofluid. An increase in the Nusselt number and friction factor with a decrease in twist ratio for BioGlycol/water and nanofluids was observed from the experiments. The maximum heat transfer enhancement of SiO2 at 2.0% volume concentration and 50oC with counter twisted tapes (CTT-5) and co-counter twisted tapes (COT-5) with twist ratio of 5 were up to 129% and 113% respectively higher than the flat tube of BioGlycol/water. Furthermore, using the TiO2 nanofluid with 1.0% volume concentration at 50oC with (CTT-5) and (COT-5) gave the maximum heat transfer enhancement up to 124% and 106% respectively higher than the flat tube of BioGlycol/water. For the case of plain tubes, it is preferable to have the flow of TiO2 and SiO2 nanofluids at 1.0% and 2.0% volume concentrations, respectively. Meanwhile, for the nanofluid flow with twisted tapes, it is recommended to use the twist ratio of 5. The use of TiO2 nanofluid with twisted tapes is preferable for volume concentrations up to 1.0%. However, the use of SiO2 nanofluid with twisted tapes is not recommended due to the lower thermal enhancement index compared to the nanofluid flow in plain tubes.